Molecular characteristics of colorectal hyperplastic polyp subgroups - Ünlü, Mehtat; Uzun, Evren; Bengi, Göksel; Sağol, Özgül; Sarıoğlu, Sülen (Turkish Journal of Gastroenterology, 2020)
Background/Aims: The importance of hyperplastic polyps during colorectal carcinogenesis is appreciated related to the understanding of serrated pathway. The morphologic subtypes of hyperplastic polyps in carcinogenesis and the nomenculature of lesions with both hyperplastic and adenomatous areas are controversial. We aimed to reveal the molecular properties of hyperplastic polyp subtypes and the molecular changes in polyps containing both hyperplastic and adenomatous areas. Matherial and Methods: 49 hyperplastic polyps [19 microvesicular (MVHP), 19 goblet-rich (GRHP), 11 mucin-poor (MPHP)] and 10 mixed hyperplastic and adenomatous polyps were analysed for KRAS, BRAF mutations and MSI with real-time PCR. Results: 68,4% of MVHPs and 81% of MPHPs which were localized in right colon had BRAF mutations. While none of the GRHPs showing a KRAS mutation with a rate of 73% was localized in the ascending colon, 63% of them were localized in the rectosigmoid area. In five (50%) of the mixed polyps, KRAS mutation was detected both in the hyperplastic and adenoma components. There was no BRAF mutation in any of the mixed polyps. However, in two cases, the hyperplastic component was MSI-H and the adenoma area was MSS. Conclusion: Hyperplastic polyps, even if smaller than 5 mm, are precancerous lesions bearing different mutations. GRHPs with predominant KRAS mutations and MVHPs and MPHSs with predominant BRAF mutations are precancerous. Although the molecular investigations for HPP/SP are not necessary the morphological subtyping should be included if the case is diagnosed with HPP/SP as it will be useful for attracting the gastroenterologist’s attention.